ANALYTICAL CENTERS IN THE UNITED STATES OF AMERICA - Mitrović, Risto (Serbian political thought, 2024)
The twentieth century in the United States of America brought numerous innovations in all aspects of social life, including politics and engagement in it. Local and state policies, which, until then, were strictly entrusted to elected officials, became the subject of interest of newly formed organizations in charge of collecting relevant data on policies, analyzing them, and, through conclusions, making recommendations on further actions needed to improve existing or create new policies in a certain sphere of politics.By looking at the century-long history of analytical centers in the United States of America, better known as "think tanks,“ it is possible to see how the changing political and socio-economic climate of the country affected the need to adapt such institutions, which gave rise to numerous new forms of activity and new spheres of interest for those centers in the USA. In addition, the development of new technologies forced the adaptation of analytical centers to them through the use of new systems for the presentation of achievements and advocating changes that their analyses deem necessary. By analyzing the methods of operation, influence of different political ideologies, various ways of research result presentation, and also how these organizations are being financed, we get a better insight into the importance of such organizations and their activities in the modern political currents of one of the most powerful countries in the world.
Keywords: analytical centers; think tanks; United States of America; politics; policy; influence